2003
DOI: 10.1093/fampra/cmg514
|View full text |Cite
|
Sign up to set email alerts
|

Trends in access to complementary or alternative medicines via primary care in England: 1995–2001 Results from a follow-up national survey

Abstract: A prior national survey of one in eight randomly selected general practices in England estimated that 39% of general practices [95% confidence interval (CI) 35-43%] provided some access to complementary or alternative medicine (CAM) therapies in 1995. A repeat survey, conducted in 2001, estimated that one in two practices in England now offer their patients some access to CAMs (95% CI 46-52%). The change was due to increased provision in-house; the proportion of practices making NHS referrals remained unchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 2 publications
1
94
0
2
Order By: Relevance
“…Environmental lead exposure has dropped in recent decades thanks to the dominant use of unleaded petrol and the ban of lead-based paint and lead solder in food cans. The general population can be exposed to lead in food and drinks, including lead-contaminated folk remedies (30)(31)(32), drinking water (33), and wine (15)(16). Strongly acidic beverages (such as wine, fruit juices, and soft drinks) and food can be contaminated with lead if stored or served in leaded crystal glassware or lead-glazed ceramics.…”
Section: Sources Of Metal Exposurementioning
confidence: 99%
“…Environmental lead exposure has dropped in recent decades thanks to the dominant use of unleaded petrol and the ban of lead-based paint and lead solder in food cans. The general population can be exposed to lead in food and drinks, including lead-contaminated folk remedies (30)(31)(32), drinking water (33), and wine (15)(16). Strongly acidic beverages (such as wine, fruit juices, and soft drinks) and food can be contaminated with lead if stored or served in leaded crystal glassware or lead-glazed ceramics.…”
Section: Sources Of Metal Exposurementioning
confidence: 99%
“…25 Indeed it was estimated that 39.5% of GP practices provided access to some form of CAM in 1995 15 and that this had risen to 50% by 2001. 26 One detailed study of those with long term conditions who use CAM concluded that such use should be understood as a critical component of self care management in general and should be viewed not as a search for a miracle cure or a rejection of conventional medicine but as an attempt to take personal responsibility for health and a pragmatic attempt at managing a chronic condition as well as possible. 14 From this perspective CAM use should be welcomed and encouraged as a good example of the kind of self management and assumption of responsibility for health which Department of Health Policy is advocating.…”
Section: Complementary Medicine Chronic Illness and Personal Budgetsmentioning
confidence: 99%
“…29,30 Whilst many GP practices provide some form of access or referral to CAM, as noted earlier, it is also the case that increasingly, such access is less likely to be funded by the NHS. 26 Following campaigns by small groups of professionals some routes of access have been cut back in recent years. Referrals to the NHS homeopathic hospitals for example, have been reduced by many PCTs.…”
Section: Complementary Medicine Chronic Illness and Personal Budgetsmentioning
confidence: 99%
“…Attempts to integrate Complementary and Alternative Medicine (CAM) into the National Health Service (NHS) have tended to be more successful within primary care than within the hospital sector, 7,19 reflecting the dominance of biomedical knowledge and power in secondary and tertiary care. 8,12,17 Nevertheless, CAM has had an increasing presence within nursing and midwifery training and practice within NHS hospitals since the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, there has been a growth in demand for CAM services from the public. 4,19 Second, practitioners themselves have been drawn to CAM: this is partly because there is a putative alignment between nursing and midwifery and CAM, in that they share an orientation towards care and holism 10 and partly because CAM has been perceived as affording an opportunity to extend and enhance their professional jurisdiction. 1,17 Such opportunities have always been somewhat uncertain, however, as there has never been a clear, governmental policy directive on the incorporation of CAM into the NHS.…”
Section: Introductionmentioning
confidence: 99%